Effect of Melatonin Supplementation on Feed, Water Intake and Body Weight in Buffalo Calves under Summer Stress - domple, vijay; A.R. Padol; C. D. Malapure; B. P. Kamdi; R.M. Sarode (Indian Journal of Animal Nutrition, 2024)
A study was undertaken to investigate the effect of melatonin supplementation on feed, water intake and body weight in buffalo calves under summer stress. Twelve healthy Murrah buffalo male calves of 6 month to 1 year age group were taken for the study. Buffalo calves were divided into control (CG) and treatment (TG) group. In TG, Melatonin (18mg/50 kg BW) was injected subcutaneously, two times at 1st and 20th day. Within and between the control and melatonin treated group the dry matter intake of buffalo calves did not differ significantly (P<0.05) during the experimental period. Within and between the control and melatonin treated group water intake of buffalo calves did not differ significantly (P>0.05) during the experiment. Within and between the control and melatonin treated group, the body weight of buffalo calves did not differ significantly (P>0.05) before start of experiment, 21 days after start of experiment and at the end of the experiment. In conclusion, the water intake and dry matter intake was at higher side in treated animals as compared to control group. It shows that during summer, buffalo calves treated with melatonin were at comfortable conditions so they were able to consume more feed and water as well.